Not Truly, Not Entirely ... Pas comme les Francophones - Roy, Sylvie (Canadian Journal of Education/Revue canadienne de l’éducation, 2010)
In this study, I investigate how French immersion students in two junior high schools in Alberta see themselves in Canadian society. The data come from three years of ethnographic research that included classroom observations and 94 interviews with students, teachers, administrators, and parents. This study shows how French immer‐ sion students do not belong to either legitimized group in Canada; they develop their own bilingual world and identities, which are not recognized in Canadian soci‐ety. I argue for inclusion of all learners of French with varying linguistic and cultural com‐ petencies in schools and workplaces so they can contribute to Canadian political, so‐ cietal, and social spheres. Key words: French immersion, bilingualism, Canadian society, inclusion, language policies Dans cette étude, l’auteure analyse comment des élèves en immersion française dans deux écoles intermédiaires de l’Alberta se perçoivent au sein de la société canadienne. Les données proviennent de trois années de recherche ethnographique, incluant des observations en classe et 94 entrevues avec des élèves, des enseignants, des adminis‐ trateurs et des parents. L’étude explique pourquoi les élèves en immersion française n’appartiennent à aucun de deux groupes de langue officielle du Canada; ces élèves développent leurs propres monde et identité bilingues, qui ne sont pas reconnus dans la société canadienne. L’auteure prône l’inclusion de toutes les personnes qui appren‐ nent le français avec divers niveaux de compétences linguistiques et culturelles dans les écoles et au travail afin qu’elles puissent apporter leur contribution aux sphères politiques, sociétales et sociales au sein du pays. Mots clés : immersion française, bilinguisme, société canadienne, politiques linguisti‐ ques